Business format in social entrepreneurships for Bangladesh's water sector - Mohammed Ziaul Hoque; Kulsuma Akter Nahid (Journal of Global Entrepreneurship Research, 2015)
This study suggests a social business format, founded on social entrepreneurship for the water sector, that appears suitable in Bangladesh. The theoretical aspect of the study examines the literature on social entrepreneurship in developing economies and in Bangladesh, as well as literature on business models and formats. The empirical aspect of the study contains individual cases that are studied through secondary data. The complete sample originates from the database of the Schwab Foundation for Social Entrepreneurship of the water sector and Bangladesh Social Enterprise Projects for social business enterprises. The results of this study provide an overview of a successful social business format composed from the nine cases of social business enterprises and the eight non-profit social enterprises in the water sector. Similarities between the social businesses' formats indicated by the social business enterprises' cross-case analysis include business mission, market exploitation, direct relationship dynamics and the basis for differentiation. When compared with the eight social business formats in the water sector, differences were found. The social business format in the water sectors does not focus on entrepreneurial skills, product innovation, direct sales, partnership with a business, or economic value creation.
Keywords: 650; Social entrepreneurship; Developing economies; Bangladesh; Water sectors